Pendidikan Alternatif dengan Model Pesantren Salafi-Khalafi (Studi Komplek R2 Pondok Pesantren Al Munawwir Krapyak Yogyakarta) - Lita Nala Fadhila (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2017)
Islamic boarding school (pesantren) is regarded as an alternative education in the midst of formal education's weaknesses that is regulated by the government. In its growth to become an alternative education, the model of salafi (traditional) pesantren has been criticised for its identity loss when it is compromised with a matter called modernity. To answer the criticism addressed to pesantren as an alternative education, complex R2 Pondok Pesantren (Islamic boarding house) al Munawwir Krapyak Yogyakarta build a pesantren education based on salafi-khalafi (traditional-modern) model. This research focuses on pesantren education based on salafi-khalafi model which is built in Complex R2 that applies pesantren education consisting of basic values, boarding house, curriculum, and the used learning methods. The education built in complex R2 becomes an alternative choice for people who want to get an education based on salafi and khalafi pesantren model at the similar time.Islamic boarding school (pesantren) is regarded as an alternative education in the midst of formal education's weaknesses that is regulated by the government because it is able to provide an education for any circles of society and it is oriented toward scientific development, intellectual aptitude, and moral building.Keywords: Pesantren, Alternative Education, Salafi-Khalafi.